Augmented inertial response of Multi-Level Converters using internal energy storage - spallarossa,C; merlin,M; Green,TC (IEEE, 2016)
During the recent years, the number of High Voltage Direct Current (HVDC) links, used for accommodating renewable energy sources and for interconnecting different power systems, has increased significantly. Apart from enhancing system stability, HVDC links can be used to provide ancillary services, such as frequency support. This paper investigates the potential of the energy storage capability of Modular Multi-level Converters (MMCs) to contribute to the frequency response. MMCs provide fast released energy through their cells capacitor that may be used to improve the system inertial response during the fault transient after a loss of generation event. To assess the effect of the converter energy storage capability, a mixed AC and DC transmission platform is developed in PowerFactory. It consists of a multi-machine system including a point-to-point MMC based HVDC link. A generation outage is applied to investigate the contribution of the MMC energy storage capability to the frequency recovery.